Perspektif Kelas Sosial pada Buku Motivasi Tak Apa-Apa Tak Jadi Apa-Apa Karya Mulasih Tary - Pamungkas, Gilang; Pamungkas, Onok Yayang (Suara Bahasa, 2024)
This research is an attempt to investigate social class differences in terms of economic status, educational status, and employment status. The method used in this research is qualitative research method. The data source used is the motivational book Tak Apa-Apa Tak Jadi Apa-Apa by Mulasih Tary published by Checklist Book in 2021. Data were collected using content analysis techniques. The findings of this study are in the form of social class differences. The data that has been obtained is processed again inductively through data reduction, data presentation, and conclusion drawing. Through a motivational book, the author presents a discourse about not being fixated on the success of others and not always comparing ourselves to the achievements of others, the most important thing is that we must be able to learn to accept ourselves, embrace ourselves, and bring ourselves to a happier path. This book illustrates the importance of self-motivation and not always looking at the success of others that can make ourselves feel like failures in living life. The results of this study are in the form of social class differences, including economic status, educational status, and employment status, which are still the benchmark for a person's existence in society. In the future, it is hoped that it will no longer reveal social class differences so as not to cause social problems.